The troubling state of India's democracy - Ganguly, Sumit; Mistree, Dinsha; Diamond, Larry (Emerging democracies, 2024)
As India's power and prominence rise on the international stage, its longstanding tradition of democracy is under threat. Since establishing a secular and democratic constitution in 1950, India has held elections at the local, state, and national levels with frequent transitions of power between opposing parties. This commitment to democracy has provided political order to a country that is twice the size of Europe and with a stunning array of social and economic divides. Despite this rich tradition, India's democracy faces an unprecedented threat with the rise of Narendra Modi and his Hindu nationalist party, the Bharatiya Janata Party. After decisively winning general elections in 2014, Modi and the BJP have pursued a range of anti-democratic policies in which the state and society are used to undermine the opposition, to stifle free speech, and to harass religious minorities. The Troubling State of India's Democracy brings together leading scholars from around the world to assess the conditions of India's democracy across three important dimensions: politics, specifically the state of political parties and the party system; the state, including the condition of federalism and the health of various institutions; and society, including NGOs, ethnic and religious tensions, and control of the media. Even though elements of India's democracy seem to function-like its commitment to elections-the contributors document a disturbing trajectory, one that not only threatens to undermine India's own stability, but could also affect the global order